Estudio del impacto socioeconómico de los proyectos ejecutados por los gobiernos parroquiales del cantón Pichincha en el período 2009-2013 - Loor Basurto, Kenia Stefanía (2014)
This research analyzed the socioeconomic impact of the projects carried out by the local government of the Pichincha Canton from 2009 to 2013; inductive- deductive method was used and observation of the programs, works and executed services. The information is related to the parishes after applying field research techniques. The information was essential to fulfill efficiently the proposed phases for this study. Using the statistical technique of Delphi, the socioeconomic indicators were defined with the sustainable development of the parishes. The sampling by Quota and convenience in the survey determined the level of acceptance of the projects; these data were tabulated in SPSS software version 11.5 and plotted in bars in Microsoft Excel. An interview with the parish government members was carried out in order to know the causes of the generated failures due to the implementation of projects in its development plan. With the information exposed above, a matrix with the priority needs of the inhabitants was done according to the socio-economic development, roads, construction of recreational areas, quality of public services, production workshops, and the attention to vulnerable sectors. Finally, the results were shared with members of the government, and a favorable response from them was achieved. Thus socio-economic development to the present sample generated a level of dissatisfaction among citizens about the impact of programs and projects.